Saudi Arabia’s Future: Will Al Saud’s Partnership with Wahhabism Hold? - Dorsey, James Michael (2016)
Saudi Arabia is confronting a perfect storm of challenges: economic, political, social, ideological, and geopolitical. How it weathers the storm will likely depend on how it handles the inevitable restructuring of the problematic partnership between the Al Saud ruling family and the Wahhabi ulama or religious scholars, on whom the former rely for their legitimacy.